2018
DOI: 10.1002/bse.2042
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of personal characteristics and gender diversity for (eco‐)innovation activities at the firm‐level: Results from a linked employer–employee database in Germany

Abstract: The burgeoning literature on the determinants of eco‐innovation has not yet considered the influence of the personal characteristics of a firm's employees. The paper opens this “black box” of unexplained heterogeneity: it has often been observed that firms with broadly similar characteristics take different decisions concerning eco‐innovations. In fact, latent variables such as the greenness of a firm may be explained by the personal characteristics (gender, family status, geographic origins, education, etc.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 71 publications
7
62
0
Order By: Relevance
“…Therefore, we are unable to generalize our findings to other jurisdictions that would have different contexts regarding either corporate governance or environmental performance. However, our findings are consistent with recent research studying board structure/gender issues and environmental performance/policy in other countries such as Australia (Galbreath, ), China (Elmagrhi et al, ), Germany (Horbach & Jacob, ), Spain (Pucheta‐Martínez & Bel‐Oms, ), and United Kingdom (Jizi, ). Future research could investigate if the same findings occur in jurisdictions with different institutional settings, especially mandatory versus voluntary quota systems.…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we are unable to generalize our findings to other jurisdictions that would have different contexts regarding either corporate governance or environmental performance. However, our findings are consistent with recent research studying board structure/gender issues and environmental performance/policy in other countries such as Australia (Galbreath, ), China (Elmagrhi et al, ), Germany (Horbach & Jacob, ), Spain (Pucheta‐Martínez & Bel‐Oms, ), and United Kingdom (Jizi, ). Future research could investigate if the same findings occur in jurisdictions with different institutional settings, especially mandatory versus voluntary quota systems.…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 92%
“…Terjesen, Aguilera, and Lorenz (2015) found that the institutional context plays a role in the number of women that sit on companies' boards. The setting for this study was the United States that has (Galbreath, 2018), China (Elmagrhi et al, 2018), Germany (Horbach & Jacob, 2018), Spain (Pucheta-Martínez & Bel-Oms, 2018), and United Kingdom (Jizi, 2017). Future research could investigate if the same findings occur in jurisdictions with different institutional settings, especially mandatory versus voluntary quota systems.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen, Leung, and Evans () further show that firms with greater representation of female directors achieve greater innovative success. In the case of environmental innovations, Horbach and Jacob () find that having a large proportion of highly qualified women and a gender‐diverse board is positively correlated with innovation activities in the environmental sector. Glass et al () propose that interlinked board members serve as a critical conduit for “mimetic pressure” in the realm of environmental practice and confirm that women board members with ties to other firms may be more influential and better able than others to successfully advocate for innovation in environmental policies and practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to literature on defining and classifying eco‐innovations (Andersen, ; Ekins, ; Epicoco, Oltra, & Saint Jean, ; Kiefer, Carrillo‐Hermosilla, Del Río, & Callealta Barroso, ; Kiefer et al, ), other key themes in the eco‐innovation literature include the drivers or determinants of eco‐innovation (del Rio, Morán, & Albiñana, ; Horbach et al, ; Triguero et al, ; Marin, ; Jové‐Llopis & Segarra‐Blasco, ; Horbach & Jacob, ; Aragon‐Correa & Leyva‐de la Hiz, ), measuring eco‐innovation (Arundel & Kemp, ), the relationship between eco‐innovation and firm performance (Aguilera‐Caracuel & Ortiz‐de‐Mandojana, ; Leyva‐de la Hiz, Ferron‐Vilchez, & Aragon‐Correa, ; Zhang & Walton, ), the relationship between eco‐innovation and competitive advantage (del Río et al, ; Ketata et al, ; Lee & Min, ; Kiefer et al, ), and the role of intermediaries (Kanda, Hjelm, Clausen, & Bienkowska, ). Although there is a literature on the different types of eco‐innovations and the classification of such, literature on how eco‐innovations are implemented (Cheng & Shiu, ; Morgan, Vorhies, & Mason, ) or managed (Suarez‐Perales, Garces‐Ayerbe, Rivera‐Torres, & Suarez‐Galvez, ) Seebode, Jeanrenaud, & Bessant, ) is scant, especially at the firm level and internally focused (Kiefer et al, ).…”
Section: Background Literaturementioning
confidence: 99%